Study of Pyrroloquinoline Quinine From Phosphate-Solubilizing Microbes Responsible for Plant Growth: In silico Approach - Bhanja, Eeshita; Das, Renuka; Begum, Yasmin; Mondal, Sunil Kanti (Frontiers in Agronomy, 2021)
Plants cannot uptake the insoluble form of phosphate from soil. Phosphate Solubilizing Microbes (PSM) release gluconic acid (C6H12O7) that is synthesized by the interaction between co-factor Pyrroloquinoline quinine (PQQ) and glucose dehydrogenase within themselves, hence convert the insoluble phosphate into a soluble form. Phylogenetic analyses based on individual sequences of PqqA-PqqE proteins involved in the PQQ biosynthetic pathway manifested clear clustering formation of the selected species according to their respective genera such as Pantoea, Rouxiella, Rahnella, Kosakonia, Mixta, Cronobacter, and Serratia. In Multiple Sequence Alignment (MSA) numerous semi-conserved sites wereidentified that indicate acquired mutation during evolution. The selected pqq genes appeared within an operon system sustain a specified order viz. pqqABCDE for both positive and negative strand. Nucleotide composition of the encoding genes displayed higher content of GCs at different positions of the codons also been properly reflected in Relative Synonymous Codon Usage (RSCU) values of the codons with few exceptions. The Correspondence Analysis (COA) based on RSCU proclaimed that the pqqB genes prefer A/U-ending codons over G/C, while for the pqqE gene; G/C-ending codons are comparatively more preferable (except CGU). Mutational pressure contributes to shaping the codon usage pattern for the selected pqq genes evinced from the COA analyses, while the ENc and neutrality plot gives attestation of natural selection. The higher values of CAI indicate the gene adaptability and codon usage bias. These comprehensive computational studies can be beneficent for further research in molecular phylogenetics, genomics, and proteomics and to better understand the evolutionary dynamics of PQQ.